Atitudes frente à homoparentalidade: uma explicação a partir de variáveis explícitas e implícitas - Freires, Leogildo Alves (2015)
The present thesis aimed at knowing the correlates and predictors of attitudes toward homosexual parenting, based on explicit and implicit variables. In order to attain this objective, five studies were conducted. Study 1 aimed at mapping participants’ opinions about child adoption by homosexual parents. Participants were 484 people from general population, with mean age of 26 years (SD = 8.31). They answered to social and demographic questions, and to a structured interview. In sum, results showed a potential acceptance of this type of adoption, as long as the parents have favorable financial, emotional and educational background. Study 2 sought to test psychometric parameters of the relevant measures. Therefore, a sample of 223 undergraduates participated, their mean age was 22 years (SD = 4.42). Participants answered to experimental versions of the following measures: Attitudes toward Homosexual Marriage Scale (ATHM) and the Sexual Prejudice Multidimensional Scale (SPMS). The main results indicated that both measures gathered preliminary evidences of validity and reliability. Study 3 aimed at gathering more robust psychometric evidences of the measures used in the previous study. Participants were 261 people from general population, with mean age of 30 years (SD = 9.35). The results confirmed the assumed factor structures for both scales, indicating psychometric adequacy of a reduced model (parsimonious). Study 4 allowed the development of an explanatory model regarding acceptance and/or opposition to homosexual parenting. Participants were 339 people from different Brazilian states, with mean age of 26 years (SD = 8.15). They answered to the short version of scales used in the previous study, and the Basic Values Survey (BVS), behavioral, and demographic variables. Results showed adequacy of two models: (1) Sexual prejudice/ Values → Acceptance of Homosexual Parenting → Homosexual parenting contact acceptance [²/df = 3.77, GFI = .99, AGFI = .93, CFI = .98, RMR = .02 e RMSEA = .09 (.023 – .163)] and (2) Sexual prejudice/ Values → Opposition of homosexual parenting → Homosexual parenting contact rejection [²/df = 4.46, GFI = .98, AGFI = .91, CFI = .97, RMR = .01 e RMSEA = .10 (.057 – .151)]. Finally, Study 5 aimed at controlling social desirability and at verifying implicit attitudes toward homosexual parenting and its value correlates. It was a quasi-experimental study with a factorial design 2x2x3. Participants were 458 people recruited online, with mean age of 23 yeas (SD = 7.6). They answered to demographic questions and to explicit and implicitmeasures. The results indicated that heterosexual parenting was considered more conventional than homosexual parenting, corroborating the hypothesis of a heterosexual norm, and an influence of normative values. In conclusion, the objectives of the present dissertation were attained, providing additional and substantial evidence to identify factors that explain attitudes toward homosexual parenting, and of the role of normative values. Nevertheless, future studies are proposed, aiming at contributing to the field.